Patient Science: Citizen Science Involving Chronically Ill People as Co-Researchers - Nils B. Heyen; Johanna Gardecki; Daniela Eidt-Koch; Miriam Schlangen; Sophie Pauly; Olaf Eickmeier; Thomas Wagner; Tanja Bratan (Journal of Participatory Research Methods)
Citizen science projects in health-related research usually follow a crowdsourcing approach where laypersons primarily have a supplying role in data collection. By contrast, this article presents an approach on a much higher engagement level (co-creation) where a team of professional and citizen scientists jointly plans, implements, and evaluates a scientific study on a chronic disease from which the citizen (patient) scientists themselves suffer. We call this approach patient science; it systematically makes use of the patients' expertise of living with the disease. This article describes the pilot project and conceptual differences compared to other participatory approaches in medical and health research. It elaborates on the implications of involving chronically ill people as co-researchers and, finally, reflects on the benefits and challenges of patient science.